Organizing identity : persons and organizations 'after theory' - Du Gay, Paul (SAGE, 2007)
This book makes a significant contribution to cultural economic approaches to organizational and economic life. Specifically it offers both a survey of the field, as well as a practical guide to doing ′cultural economy′. The text, which builds upon du Gay′s earlier work, will engage with a range of debates from cultural studies, sociology, anthropology, geography, and management. It brings du Gay′s style and originality to bear on the subject of culture and economy, and results in a book that will once more make a solid contribution to cultural studies.